Persepsi Bimbingan Pribadi Sosial Dan Sikap Sosial Dengan Kepercayaan Diri - Anita Dewi Astuti; Septy Sumaryani (ILIN Institute Makassar, 2020)
The purpose of this study is to determine the relationship between perceptions of social guidance and social attitudes with the confidence of class XI's students of SMA Negeri 1 Kokap Kulon Progo. This study uses a quantitative approach with correlational research type with a research subject of 55 students. The data analysis technique uses current product display techniques, without partials and without doubles. From the analysis of the coefficient of determination (R2) = 0.596, which means that the perception of personal guidance and social attitudes together contributes to self-confidence by 59.6% and the remaining 40.4% is caused by other variables outside the perception of social personal guidance. and social attitudes. This study provides an overview of guidance and counseling teachers about personal social guidance, social attitudes and self-confidence. Based on the results of this study, it can be used as material for consideration in developing guidance and counseling service programs according to the needs of students in schools